Retirement blues - Gabriel Heller-Sahlgren (Research Institute of Industrial Economics (IFN), 2016)
This paper analyses the short- and long-term effects of retirement on mental health in ten European countries. It exploits thresholds created by regular state pension ages in a fuzzy regression-discontinuity design combined with individual-fixed effects to deal with endogeneity in retirement behaviour. The results display no short-term effects of retirement on mental health, but a large negative longer-term impact. This impact survives a battery of robustness tests, and applies to women and men as well as to people of different educational backgrounds equally. Differences compared to previous research are attributed to the study's differentiation of short- and longer-term effects as well as its utilisation of a cleaner research design. Overall, the paper's findings suggest that reforms inducing people to postpone retirement are not only important for making pension systems solvent, but with time could also pay a mental health dividend among the elderly and reduce public health care costs.
Keywords: I10; J14; J26; 330; Mental Health; Retirement; SHARE; Regression-Discontinuity Design